Initial versus longer‐term effects of tadpole declines on algae in a Neotropical stream. (13th March 2014) - Connelly, Scott; Pringle, Catherine M.; Barnum, Thomas; Hunte‐Brown, Meshagae; Kilham, Susan; Whiles, Matt R.; Lips, Karen R.; Colón‐Gaud, Checo; Brenes, Roberto
Summary Information about temporal patterns of ecological responses to species losses is integral to our understanding of the ultimate effects of declining biodiversity. As part of the Tropical Amphibian Declines in Streams (TADS) project, we quantified changes in algal biomass and N cycling in algae in upland Panamanian streams following the widespread decline of larval anurans. Reach‐scale monitoring during and after a catastrophic, disease‐driven amphibian decline showed significant 2.8‐fold increases (P < 0.05) in algal biomass in pools and 6.3‐fold increases in riffles in the 5 months following the decline. 3 years after the decline, the magnitude of this initial change dampened to increases (P < 0.05) of 2‐fold in pools and 3.5‐fold in riffles over pre‐decline levels. Similarly, total organic matter of benthic biofilms, measured as ash‐free dry mass (AFDM), increased significantly by 2.2‐fold in pools and 2.3‐fold in riffles in the initial 5‐month post‐decline period, with the magnitude of these changes dampening slightly to a 2‐fold increase in pools and 1.9‐fold increase in riffles over pre‐decline levels after 3 years (P < 0.05 for differences at 5 months and 3 years). There were initial increases (P < 0.05) in Chl a:AFDM ratios 5 months after the decline, but ratios had returned to pre‐decline levels after 3 years. Algal food quality (as C/N) increased slightly, but not significantly, during the initial 5‐month post‐decline period and remained constant over 3 years. Mean δ15N in biofilms in pool habitat (measured over the reach scale) was significantly depleted initially following tadpole declines and remained significantly depleted 3 years after the decline (4.34 ‰ pre‐ versus 3.24‰ post‐; P < 0.05), suggesting that the loss of tadpoles reduced N recycling. Increases in abundance and production of some grazing macroinvertebrate taxa after the decline may have contributed to the gradual reduction in the difference between initial and longer‐term post‐decline algal biomass. However, algal biomass was still 2‐fold greater than pre‐decline levels after 3 years, indicating that grazing macroinvertebrates did not fully compensate for the loss of tadpoles.